Retrospective Study on Amount of Local Anaesthesia Used in Extraction of Mandibular Third Molar Impaction Based on Winters Classification - M, ASHFAQ AHMED.; D, PRADEEP; DINESH, S.P. SARAVANA (The journal of contemporary issues in business and government, 2021)
Local anaesthesia are most commonly used drugs in dentistry. The required dose of local anaesthesia is based on factors like age, weight, systemic illness etc. Failure to administer the right amount may lead to adverse effects. Mandibular third molar is a common tooth to get impacted and due to which discomfort,pain and also caries in adjacent teeth occurs.Thus the aim of the study is to determine the amount of local anesthesia used in extraction of mandibular third molar. Evaluation of 634 patients reported to saveetha dental college for extraction of mandibular third molar. Data was collected from dental archiving software and the results were statistically analysed. From the results obtained, we can observe that impactions which use 0-2ml of local anaesthesia are mesioangular(28.01%), Distoangular impaction (8.79%), Horizontal impaction(21.01%), vertical impaction (6.35%), and impactions which use 3-5 ml are mesioangular(12.87%), Distoangular impaction (5.37%), Horizontal impaction(12.21%), vertical impaction (3.58%) and impactions which use 6-10 ml are mesioangular(1.30%), vertical impaction (0.33%) and the type of impaction which uses more amount of local anaesthesia was found to be mesioangular impaction but the results obtained are found to be statistically not significant(p>0.05). According to the age distribution, patients who use 0-2 ml of local anaesthesia belong to the age group of 17-25 years (23.78%), 26-35 years(28.50%), 36-45 years(8.41%), 45- 65 years(3.75%) and patients who use 3-5ml of local anaesthesia belong to the age group of 17-25 years (12.87%), 26-35 years(15.64%), 36-45 years(4.56%), 45-65 years(0.98%) and the patients of age group 17-25 years use maximum dose of local anaesthesia but the results obtained are statistically insignificant (p>0.05). Within the limits of the study, we can conclude that mesioangular impaction is the common impaction that uses a maximum dose of 6-10 ml and age groups of 26-35 years use more LA upto 5ml and ages 17-25 years use a maximum of 6-10 ml.